Clinical features of the myasthenic syndrome arising from mutations in GMPPB. Issue 8 (4th May 2016) - Rodríguez Cruz, Pedro M; Belaya, Katsiaryna; Basiri, Keivan; Sedghi, Maryam; Farrugia, Maria Elena; Holton, Janice L; Liu, Wei Wei; Maxwell, Susan; Petty, Richard; Walls, Timothy J; Kennett, Robin; Pitt, Matthew; et al.
Abstract : Background: Congenital myasthenic syndrome (CMS) due to mutations in GMPPB has recently been reported confirming the importance of glycosylation for the integrity of neuromuscular transmission. Methods: Review of case notes of patients with mutations in GMPPB to identify the associated clinical, neurophysiological, pathological and laboratory features. In addition, serum creatine kinase (CK) levels within the Oxford CMS cohort were retrospectively analysed to assess its usefulness in the differential diagnosis of this new entity. Results: All patients had prominent limb-girdle weakness with minimal or absent craniobulbar manifestations. Presentation was delayed beyond infancy with proximal muscle weakness and most patients recall poor performance in sports during childhood. Neurophysiology showed abnormal neuromuscular transmission only in the affected muscles and myopathic changes. Muscle biopsy showed dystrophic features and reduced α-dystroglycan glycosylation. In addition, myopathic changes were present on muscle MRI. CK was significantly increased in serum compared to other CMS subtypes. Patients were responsive to pyridostigimine alone or combined with 3, 4-diaminopyridine and/or salbutamol. Conclusions: Patients with GMPPB-CMS have phenotypic features aligned with CMS subtypes harbouring mutations within the early stages of the glycosylation pathway. Additional features shared with the dystroglycanopathies include myopathic features, raised CK levels and variable mild cognitive delay. This syndrome underlines that CMS can occur in the absence of classic myasthenic manifestations such as ptosis and ophthalmoplegia or facial weakness, and links myasthenic disorders with dystroglycanopathies. This report should facilitate the recognition of this disorder, which is likely to be underdiagnosed and can benefit from symptomatic treatment.